Hydrogels Improve Plant Growth in Mars Analog Conditions - Peyrusson, Frédéric (Frontiers in Astronomy and Space Sciences, 2021)
Sustainable human settlement on Mars will require in situ resource utilization (ISRU), the collection and utilization of Mars-based resources, including notably water and a substrate for food production. Plants will be fundamental components of future human missions to Mars, and the question of whether Mars soils can support plant growth is still open. Moreover, plant cultivation may suffer from the lack of in situ liquid water, which might constitute one of the biggest challenges for ISRU-based food production on Mars. Enhancing the crop yield with less water input and improving water utilization by plants are thus chief concern for sustainable ISRU food production. Hydrogels are polymers able to absorb large quantity of water and to increase soil water retention, plant establishment and growth. This work reports on the short-term assessment of plant growth in Mars soil analogs supplemented with hydrogels. Soil analogs consisted of sand and clay-rich material, with low organic matter content and alkaline pH. Soils were supplemented with 10% (w/w) potting medium and were sampled in Utah desert, in the vicinity of the Mars Desert Research Station, surrounded by soils sharing similarities in mineralogical and chemical composition to Martian soils. Height and dry biomass of spearmint (Mentha spicata) were compared under various irrigation frequencies, and seed germination of radish (Raphanus sativus) were monitored. Under limited irrigation, results indicate that the soil analogs were less capable of supporting plant growth as a comparison to potting medium. The effects of hydrogel supplementation were significant under limited irrigation and led to spearmint heights increased by 3 and 6% in clay- and sand-containing soils, respectively. Similarly, hydrogel supplementation resulted in spearmint mass increased by 110% in clay-containing soils and 78% in sand-containing soils. Additionally, while radish seeds failed to germinate in soil analogs, hydrogel supplementation allows for the germination of 27% of seeds, indicating that hydrogels might help loosening dense media with low water retention. Collectively, the results suggest that supplementation with hydrogel and plant growth substrate could help plants cope with limited irrigation and poor alkaline Mars soil analogs, and are discussed in the context of strategies for ISRU-based off-world colonization.